3D printing of gelatin methacrylate-based nerve guidance conduits with multiple channels. (July 2020) - Ye, Wensong; Li, Haibing; Yu, Kang; Xie, Chaoqi; Wang, Peng; Zheng, Yating; Zhang, Peng; Xiu, Jingfang; Yang, Yi; Zhang, Feng; He, Yong; Gao, Qing
Abstract: Methods in nerve tissue engineering for peripheral nerve regeneration have recently focused on the application of rapid three-dimensional (3D) printing with resorbable and degradable biomaterial ink. The technique aims to design and fabricate nerve guidance conduits (NGCs) to repair large-gap nerve injuries. In this study, Digital light processing (DLP)-based printing of multichannel NGCs for peripheral nerve regeneration by using gelatin methacrylate (GelMA) hydrogels was presented. Multichannel NGCs with different inner diameters were successfully fabricated using desired patterns, and optimal printing parameters were investigated. In vitro co-culturing of PC12 cells demonstrated that NGCs supported the survival, proliferation, and migration of neural cells along the longitudinal channel. The results also showed that neural crest stem cells could be induced to differentiate into neurons on fabricated conduits. This method will provide a rapid and accurate manner to fabricate complex NGCs, which can be potentially used to repair peripheral nerves. Graphical abstract: Unlabelled Image Highlights: NGCs with multiple channels were fabricated by DLP-based 3D printing with GelMA. NGCs could support the survival, proliferation, and migration of neural cells. Neural crest stem cells could differentiate into neurons on the conduits.